Dissecting chromatin interactions in living cells from protein mobility maps - Erdel, Fabian; Müller-Ott, Katharina; Baum, Michael; Wachsmuth, Malte; Rippe, Karsten (Chromosome research, 2011)
The genome of eukaryotes is organized into a dynamic nucleoprotein complex referred to as chromatin, which can adopt different functional states. Both the DNA and the protein component of chromatin are subject to various post-translational modifications that define the cell’s gene expression program. Their readout and establishment occurs in a spatio-temporally coordinated manner that is controlled by numerous chromatin-interacting proteins. Binding to chromatin in living cells can be measured by a spatially resolved analysis of protein mobility using fluorescence microscopy based approaches. Recent advancements in the acquisition of protein mobility data using fluorescence bleaching and correlation methods provide data sets on diffusion coefficients, binding kinetics, and cellular concentrations on different time and length scales. The combination of different techniques is needed to dissect the complex interplay of diffusive translocations, binding events, and mobility constraints of the chromatin environment. While bleaching techniques have their strength in the characterization of particles that are immobile on the second/minute time scale, a correlation analysis is advantageous to characterize transient binding events with millisecond residence time. The application and synergy effects of the different approaches to obtain protein mobility and interaction maps in the nucleus are illustrated for the analysis of heterochromatin protein 1.
Published: 17 September 2010
Gesehen am 29.04.2022